Hypoglossal Nerve Stimulator Implantation in an Ambulatory Surgery Center Versus Hospital. (24th September 2021) - Morse, Elliot; Han, Catherine; Suurna, Maria
Abstract : Objectives/Hypothesis: Hypoglossal nerve stimulator (HGNS) implantation is highly effective in treating obstructive sleep apnea (OSA) in select patient populations that are intolerant of continuous positive airway pressure. Implantation surgery is traditionally performed in hospital outpatient departments (HOPD) due to concern about anesthetic effects and airway manipulation in an OSA population. In this study, we examined complications and efficiency of HGNS implantation in an ambulatory surgery center (ASC) versus HOPD. Study Design: Retrospective cohort study. Methods: Patients with HGNS implantation performed between May 2015–January 2021 at our HOPD or ACS were included. Patient‐related characteristics, surgical times, and postoperative complications were obtained via chart review. Reimbursement data on a national level for Medicare patients were calculated based on publicly available data from the Center for Medicare Services. Patient characteristics, surgical times, and complications were summarized as medians with interquartile ranges (IQRs) and proportions in each surgical setting group as appropriate. These were compared between surgical setting groups via Wilcoxon rank‐sum testing and χ 2 testing. Results: A total of 122 patients were included. Patients in the HOPD group had significantly higher median apnea‐hypopnea index (AHI) (42.0 [IQR 27.9–51.0]) compared to the ASC group (31.0 [IQR 21.0–44.2], P = .005). The intervals between in‐room and case start, case finish and out‐of‐room, and time in the postoperative area were significantly shorter in the ASC group compared to the HOPD group. Reimbursement on a national level was estimated at 18% lower for patients with surgery performed at the ASC. There was no significant difference in postoperative complications. Conclusions: HGNS implantation in an ASC is safe and more efficient than in a HOPD, and may also be more cost‐effective. Level of Evidence: 3 Laryngoscope, 132:706–710, 2022